Hubungan Antara Obesitas Sentral dengan Kadar Glukosa Darah Puasa Anak Usia 10-12 tahun - , Ernawati Kusumaningrum,dr.,S.Ked.; , dr. Endy Paryanto P, MPH SpA.(K), ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Obesity in children has now reached epidemic levels. The cause of obesity is multifactorial. One consequence of obesity is the occurrence of impaired fasting glucose even type 2 diabetes mellitus through mechanisms of insulin resistance. The purpose of this study was to determine the relationship between obesity and fasting blood glucose levels in children age 10-12 years. This study was part of a multicenter study to determine the prevalence of obesity in primary school children in several major cities in Indonesia. We conducted a cross-sectional study examining fasting blood glucose levels in 53 obese group and 53 non-obese group children age 10-12 years. There are 8 (7.5%) children in the obese group and 7 (6.6%) children in nonobese group with impaired fasting glucose. No child with type 2 diabetes was in both groups. The risk of impaired fasting glucose in the obese group was 1.14 times (95% CI: 0.35 to 3.96) than non-obese group. Based on the ratio of waist circumference to height, risk of impaired fasting glucose in the central obesity group was 1.21 times (95% CI: 0.98 to 2.94) than non central obesity group.